Attitudes Toward Dialectal Variations in Saudi Arabic: A Case Study of King Abdulaziz University Students - Saeed Ali Al Alaslaa (Languages)
The current study investigated the attitudes of 340 Saudi college students towards two Arabic dialectal variations, kaskasah and kaʃkaʃah, utilizing the matched-guise technique. Participants listened to recordings of a speaker using each variation and evaluated the speaker on various personality traits, regional origin, and hireability. The findings revealed generally positive attitudes towards both variations, with the majority associating the speaker with desirable traits such as humility, kindness, friendliness, and respectfulness. However, the kaskasah variation was perceived slightly more favorably overall compared to kaʃkaʃah. The study also found distinct regional associations, with kaskasah slightly more strongly linked to the Najdi dialect and kaʃkaʃah overwhelmingly associated with the Southern dialect. Notably, a considerable minority indicated that they would not hire speakers of these variations, particularly kaʃkaʃah, suggesting some degree of dialect-based bias. The study contributes to research on language attitudes in Saudi Arabia by highlighting the complex interplay between dialectal variation, regional identity, and social evaluation. The findings underscore the importance of promoting linguistic awareness and inclusivity to mitigate the negative effects of dialect-based stereotyping and bias.